A Roman financier’s Version of Euergetism: C. Vibius Salutaris and Ephesos - Kokkinia, Christina (Tekmeria, 2019)
Based on a close study of the text of the epigraphic dossier IEph 1a 27, dated 104 CE, that once covered an entire wall at Ephesos’ theatre and is now in the British Museum and, in addition, on the evidence of other inscriptions relating to C. Vibius Salutaris, this paper argues that: contrary to a widely held view, Salutaris was not an Ephesian by birth; that the terms of his foundation gave him absolute control over the foundation’s capital; that the objects donated and the rituals in which they featured were so designed as to bestow disproportionately great honor on the founder. Salutaris’ interpretation of euergetism was unconventional and his gifts to Ephesos would most likely have sunk in oblivion, were it not for his connections to representatives of the Roman state, and, most importantly, for his foundation’s successful advertising of Ephesos’ attachment to Rome.